2022
DOI: 10.1101/2022.02.21.22271241
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the heterogeneity in the transmission of infectious diseases from time series of epidemiological data

Abstract: Structural features and the heterogeneity of disease transmissions play an essential role in the dynamics of epidemic spread. But these aspects can not completely be assessed from aggregate data or macroscopic indicators such as the effective reproduction number. We propose an index of effective aggregate dispersion (EffDI) that indicates the significance of infection clusters and superspreading events in the progression of outbreaks by carefully measuring the level of stochasticity in time series of reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Another common method of allowing for transmission heterogeneity is an instant-level heterogeneity model [ 22 , 25 ]. This model extended the standard model ( 1 ) by replacing the instantaneous reproduction number R t with an instant-related random variable η t for all the infected cases, that is, where Γ(⋅, ⋅) stands for Gamma distribution in the shape-rate parameterizations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another common method of allowing for transmission heterogeneity is an instant-level heterogeneity model [ 22 , 25 ]. This model extended the standard model ( 1 ) by replacing the instantaneous reproduction number R t with an instant-related random variable η t for all the infected cases, that is, where Γ(⋅, ⋅) stands for Gamma distribution in the shape-rate parameterizations.…”
Section: Methodsmentioning
confidence: 99%
“…Several tools for the estimating of real-time reproduction number based on incidence data had been developed with successful applications [19][20][21], but the study on realtime transmission heterogeneity is so far rather limited. In some recent studies, researchers suggested the relationship between the transmission heterogeneity and the incidence over an epidemic [22][23][24][25], but none have attempted to accurately delineate the heterogeneity with incidence data and to compare with those records in literatures. In this study, we attempted to develop a simple method to estimate the transmission heterogeneity on the basis of incidence data.…”
Section: Introductionmentioning
confidence: 99%
“…Another common method of allowing for transmission heterogeneity is an instant-level heterogeneity model [22, 25]. This model extended the standard model (1) by replacing the instantaneous reproduction number R t with an instant-related random variable for all the infected cases, that is, where Γ(·, ·) stands for Gamma distribution in the shap e-rate parameterizations.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the composite rate under this model is . And the incidence I t is Negative Binomial distribution as (NegB indicating Negative Binomial distribution ): This model accounted for the variation in infectiousness at different times, which could be useful in epidemic forecasting in the long term [22, 25]. But this model overlooked the variation in infectiousness of different infectious individuals, and hence failed to identify the exact degree of heterogeneity from incidence data (showed in Results).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation